Scintillation proximity assay for DNA binding by human p53 - Susannah Gal; Jeffery R. Cook; Leighton Howells (BioTechniques)
Many DNA binding proteins are known to regulate gene expression. When that binding is altered, a disease state can result. A common method for measuring DNA binding, namely electrophoretic mobility shift assay (EMSA) is often used but it is not amenable to rapid screening of many samples. As an alternative method, we have developed a DNA binding assay for the tumor suppressor protein p53 in a 96-well microtiter plate format using scintillation proximity assay (SPA) beads. We have shown this assay to be sensitive (as little as 0.5 ng p53 can be detected), quick (assay completed in as little as 15 min), and easily quantitated using a microtiter plate scintillation counter. We also used the assay to analyze the kinetics of the DNA binding to p53. The specificity of this p53 DNA binding SPA was confirmed using competition by oligonucleotides either from the same gene or from mutated versions of this sequence. Thus, SPA is a good alternative to gel shift assays for DNA binding and may be useful for the analysis of multiple tumor cell samples or for high-throughput screens for compounds affecting DNA binding by proteins of interest.